The hepatic microenvironment and immune cell recruitment in colorectal liver metastasis - ALMUAILI, DALAL (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2020)
The liver is uniquely enriched with anti-tumour immune cells. However, liver metastasis is anticipated in over half of colorectal cancer patients. The value of the type and location of immune cells to prognosis has been well established in colorectal cancer, but is not clear in colorectal-liver metastasis (CRLM). We hypothesized that the immune repertoire is altered in CRLM, and that effector T-cells correlate to prognosis. To investigate this, paraffin embedded tumour and tumour adjacent tissues from patients (n=62) who underwent resection for CRLM, and donor (n=14) liver tissues collected during liver transplantation were recalled. CD45 (pan leukocyte marker), CD3 (T-cells), and CD8 (cytotoxic T-cells) were localised by immunohistochemistry and quantified. In donor liver tissue, leukocytes and T-cells were found to accumulate around portal triads compared to the parenchyma. In CRLM tissue, leukocytes and T-cells accumulated at the invasive margin separating tumour from morphologically normal adjacent tissue. These cells appeared to penetrate the tumour tissue through several defined penetration points at the invasive margin, an observation not previously described. Average absolute cell counts for all three markers were found to be significantly altered in CRLM tissue compared to donor liver (CD45 P< 0.0001, CD3 P< 0.0001, CD8 P< 0.0001) with significant interpatient variation. High vs low immune recruiters were defined by the median cell counts within tumours, and were found to significantly correlate with overall survival (CD3 P=0.04, CD8 P=0.006). The numbers of tumour infiltrating immune cells affects survival, and cellular trafficking is dictated by chemokines which might provide novel immunotherapeutic targets. We hypothesized that dysregulation in chemokines compromises immune infiltration and may explain low survival in the group of CRLM patients with low T-cell infiltration. Fresh liver tissue was obtained from CRLM resections (n=15), and during liver transplantations (n=14) for flow cytometry, and protein analysis. Levels of CCL8, the monocyte chemoattractant, were significantly higher in the xiv tumour (155.4?31.4 pg/mg of protein) compared to donor liver (39.6?9.3 pg/mg of protein; p=0.003), with significant interpatient variation. Levels of CXCL9, the T-cell chemoattractant, were significantly higher in the tumour (282.3?22.5 pg/mg of protein) compared to donor liver (172.9?21 pg/mg of protein; p=0.003), with significant interpatient variation. Blocking CXCL9 significantly reduced chemotaxis of leukocytes (P=0.04) and CD8 cells (P=0.04) in response to tumour conditioned media. In summary, we demonstrated a prognostic value for immune infiltration in CRLM patients. We highlighted the significance of CXCL9 in T-cell migration. Cancer therapy has been revolutionized by the possibilities of manipulating the immune system; CXCL9 may present a novel immunotherapeutic target for colorectal liver metastases.
APPROVED
Keywords: colorectal liver metastases; leukocytes; T-lymphocytes; cytotoxic T cells; CXCL9; chemotaxis; patient survival